Did introducing Twitter and digital professionalism as an assessed element of the nursing curriculum impact social media related incidence of 'Fitness to Practise': 12-year case review. (January 2021) - Jones, Sharon; Chudleigh, Meriel; Baines, Rebecca; Jones, Ray B.
Abstract: Many educators argue for the benefits of nursing students engaging with social media but some have concerns about inappropriate use. In 2014, we introduced Digital Professionalism, a mandatory curriculum innovation including assessed Twitter use, for nursing but not midwifery students. British nursing students who display unprofessional behaviour are subject to 'Fitness to Practise' hearings. We aimed to use routinely collected data to see if inappropriate social media use had increased from introducing Twitter to the curriculum. We used data (2008–2019) on Fitness to Practise cases for nine completing cohorts comprising 4398 nursing and 338 midwifery students. We compared annual Fitness to Practise incidence rates related to social media between cohorts with and without mandatory Twitter. There was no difference in the number of nursing students involved with social media cases before (7/2636 (0.3%)), and after (10/1762 (0.6%)) the introduction of Twitter. Nursing students, after introduction of Twitter, were no more likely than midwifery students (no introduction of Twitter), to misuse social media. Fitness to Practise hearings related to social media were highly infrequent. Our study supports the argument that benefits for most nursing students of introducing professional use of social media are not negated by increased inappropriate use. Highlights: Unique study of incidence of Fitness to practise cases over many years. Benefits of introducing Twitter to undergraduate curriculum outweigh any problems. Fitness to practise cases did not increase after introducing obligatory Twitter use. Few fitness to practise cases involved misusing social media. The few misuses of social media were on Snapchat and Facebook, not Twitter.